Neural Basis of Video Gaming: A Systematic Review - Palaus, Marc; Marron, Elena M.; Viejo-Sobera, Raquel; Redolar-Ripoll, Diego (Frontiers in Human Neuroscience, 2017)
Background Video gaming is an increasingly popular activity in contemporary society, especially among young people, and video games are increasing in popularity not only as a research tool but also as a field of study. Many studies have focused on the neural and behavioral effects of video games, providing a great deal of video game derived brain correlates in recent decades. There is a great amount of information, obtained through a myriad of methods, providing neural correlates of video games. Objectives We aim to understand the relationship between the use of video games and their neural correlates, taking into account the whole variety of cognitive factors that they encompass. Methods A systematic review was conducted using standardized search operators that included the presence of video games and neuro-imaging techniques or references to structural or functional brain changes. Separate categories were made for studies featuring Internet Gaming Disorder and studies focused on the violent content of video games. Results A total of 116 articles were considered for the final selection. One hundred provided functional data and twenty two measured structural brain changes. One-third of the studies covered video game addiction, and 14% focused on video game related violence. Conclusions Despite the innate heterogeneity of the field of study, it has been possible to establish a series of links between the neural and cognitive aspects, particularly regarding attention, cognitive control, visuospatial skills, cognitive workload and reward processing. However, many aspects could be improved. The lack of standardization in the different aspects of video game-related research, such as the participants’ characteristics, the features of each video game genre and the diverse study goals could contribute to discrepancies in many related studies.